(untitled) (Social and Environmental Law Journal, 2023)
The main focus of this research is to discuss the right to sustainability within Brazilian society and to expose the fashion industry as one of the biggest problems, putting as one of the solutions, the method known as 4D Flownomy. The methodology used was bibliographic research, in order to analyze the impact of fashion on the environment, resulting in the need for commitments by major brands to reduce CO2 emissions, in addition to aligning with the Sustainable Development Goals of the Agenda 2030 of the UN.